Design and synthesis of novel bis-annulated caged polycycles via ring-closing metathesis: pushpakenediol - Sambasivarao Kotha; Mirtunjay Kumar Dipak (Beilstein Journal of Organic Chemistry, 2014)
Intricate caged molecular frameworks are assembled by an atom economical process via a Diels–Alder (DA) reaction, a Claisen rearrangement, a ring-closing metathesis (RCM) and an alkenyl Grignard addition. The introduction of olefinic moieties in the pentacycloundecane (PCUD) framework at appropriate positions followed by RCM led to the formation of novel heptacyclic cage systems.